A Randomized, Double-Blind, Placebo-Controlled, Multi-Centered Clinical Study to Evaluate the Efficacy and Safety of Artemisia annua L. Extract for Improvement of Liver Function - Han, Byoungduck (Clin Nutr Res, 2020)
Non-alcoholic fatty liver disease (NAFLD) has the potential to develop into hepatic steatosis and progress to terminal liver diseases such as cirrhosis and hepatocellular carcinoma. This human clinical study was aimed to demonstrate that SPB-201 (powdered-water extract of Artemisia annua) can improve liver function in subjects with non-alcoholic liver dysfunction at mild to moderate levels. A decrease of 271% in aspartate aminotransferase (AST) level and a significant decrease of 334% in alanine aminotransferase (ALT) level was observed in the test group as compared to the control group at the 4 weeks follow-up. In addition, after 8 weeks, decreases of 199% in AST level and 216% in ALT level were reported in the test group as compared to the control group. These results confirmed that SPB-201 intake significantly enhanced liver function and health. Moreover, the Multidimensional Fatigue Scale score of the test group decreased but that of the control group increased, implicating that SPB-201 also eliminated overall fatigue. No significant adverse events were observed among all subjects during the study. Taken together, our clinical study confirmed the excellent efficacy and safety of SPB-201 in liver function improvement, showing the possibility of SPB-201 as a functional food to restore liver dysfunction and treat liver diseases.